2020
DOI: 10.21203/rs.3.rs-51189/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Automatic Arrhythmia Detection Using One-Dimensional Convolutional Neural Network

Abstract: Background: Cardiovascular diseases (CVDs) are common diseases that pose significant threats to human health. Statistics have demonstrated that a large number of individuals die unexpectedly from sudden CVDs. Therefore, real-time monitoring and diagnosis of abnormal changes in cardiac activity are critical, as they can help the elderly and patients handle emergencies in a timely manner. To this end, a round-the-clock electrocardiogram (ECG) monitoring system can be developed with the quick detection of an ECG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…To the best of our knowledge, our transfer learning model performance (AUC = 0.906) is the highest compared to other studies using transfer learning and Kaggle datasets (31)(32) as shown in Table-2. Our AUC performance using the Kaggle dataset was also higher compared to performance metrics on the ADNI dataset, likely due to the fact that the Kaggle dataset had 2.5 times the number of images as the ADNI dataset.…”
Section: Discussionmentioning
confidence: 70%
“…To the best of our knowledge, our transfer learning model performance (AUC = 0.906) is the highest compared to other studies using transfer learning and Kaggle datasets (31)(32) as shown in Table-2. Our AUC performance using the Kaggle dataset was also higher compared to performance metrics on the ADNI dataset, likely due to the fact that the Kaggle dataset had 2.5 times the number of images as the ADNI dataset.…”
Section: Discussionmentioning
confidence: 70%
“…Many articles present the utilization of a CNN to classify arrhythmias, although none of them includes a class for individuals suffering from ARVC. An 1D‐CNN is utilized to classify normal and abnormal ECG heartbeats into three classes, 28,29 while in References 30,31 the classification concerns one and two additional types of arrhythmias respectively. Other articles highlight the usage of 2D‐CNNs for multiclass heartbeat classification, for example, Reference 32 proposes a 11‐layer 2D‐CNN to classify ECGs belonging to MIT‐BIH arrhythmia database into normal, supraventricular, ventricular, fusion and unknown class with 98.3% accuracy, while a 5 class classification of arrhythmias based on a 2D‐CNN is also presented in References 33,34.…”
Section: Introductionmentioning
confidence: 99%